2017
DOI: 10.1101/235267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germ layer specific regulation of cell polarity and adhesion gives insight into the evolution of mesoderm

Abstract: Summary 25In triploblastic animals, Par proteins regulate cell-polarity and adherens junctions of both 26 ectodermal and endodermal epithelia. But, in embryos of the diploblastic cnidarian Nematostella 27 vectensis, Par proteins are eliminated altogether in the bifunctional endomesodermal epithelia. 28Using immunohistochemistry, CRISPR/Cas9, and overexpression of specific mRNAs, we describe 29 the functional association between Par proteins, ß-catenin, and snail genes in N. 30vectensis embryos. We demonstrate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 67 publications
(122 reference statements)
0
9
1
Order By: Relevance
“…Thus, it is possible that endodermal epithelia are intrinsically different in the way that they polarise. In support of this view, it has recently been found that PAR-3, PAR-6, and aPKC are degraded in the invaginating endomesoderm of the Cnidarian Nematostella vectensis and are not required for this tissue to form an epithelium [ 67 ]. Thus, the difference between endodermal and ectodermal polarity systems may have evolved before the origin of Bilateria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that endodermal epithelia are intrinsically different in the way that they polarise. In support of this view, it has recently been found that PAR-3, PAR-6, and aPKC are degraded in the invaginating endomesoderm of the Cnidarian Nematostella vectensis and are not required for this tissue to form an epithelium [ 67 ]. Thus, the difference between endodermal and ectodermal polarity systems may have evolved before the origin of Bilateria.…”
Section: Discussionmentioning
confidence: 99%
“…In bilaterians and cnidarians, the apical localization of MlPar-6 induces the phosphorylation of MlPar-1, displacing this protein to basolateral cortical regions 4,5,21,22 . Using our specific MlPar-1 antibody, we characterized the subcellular localization of the MlPar-1 protein during the early M. These results were also supported in vivo when we overexpressed the mRNA encoding for MlPar-1 fused to mCherry (MlPar-1-mCherry) into M. leidyi embryos by microinjection ( Figure 3 To discount the possibility that the observations recorded in vivo for both MlPar-6-mVenus and MlPar-1-mCherry proteins are caused by a low-quality mRNA or lack of structural conservation, we overexpressed each ctenophore mRNA into embryos of the cnidarian Nematostella vectensis and followed their localization by in vivo imaging (Figure 4).…”
Section: Mlpar-1 Remains Cytoplasmic During Early M Leidyi Developmentmentioning
confidence: 99%
“…While the asymmetric cortical distribution of the Wnt Planar Cell Polarity (PCP) pathway components polarizes the cells along the tissue plane, the asymmetric cortical distribution of Par system components polarizes the cells along the apical-basal axis 2,3,[13][14][15][16][17][18][19][5][6][7][8][9][10][11][12] . The mechanisms that organize cell-polarity are highly conserved in all animals that have been studied and most likely been present in the most recent common ancestor (MRCA) of Cnidaria and Bilateria 3,5,9,11,[20][21][22][23] ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, N. vectensis has become an established cnidarian model in developmental biology due to its relative ease of laboratory spawning 14,15 , tractable developmental biology [16][17][18][19][20] , extensive regenerative capacity [21][22][23][24] , and robust molecular genetic approaches [25][26][27][28][29] . Nematostella polyps can harbor a variable number of tentacles ranging from 4 to 18, but the common number in adulthood is 16 (refs.…”
mentioning
confidence: 99%